Quantitative estimation of cilnidipine and valsartan in rat plasma by RP-HPLC: its pharmacokinetic application - Ramanlal N. Kachave; Shanker S. Yelmame; Akshay G. Mundhe (SpringerOpen, 2021)
Abstract Background Cilnidipine (CLD) and valsartan (VAL) are antihypertensive agents used in the treatment of hypertension. So, pharmacokinetic study of CLD and VAL in rat plasma was carried out using chromatographic method. The chromatographic separation was performed on the Inertsil ODS column, using mobile phase methanol: water 85:15 v/v (pH 3.0) at the flow rate of 1.1 mL/min., detected at 254 nm. Result Cilnidipine (CLD) (1 mg/kg) and valsartan (VAL) (1 mg/kg) was administered orally in rats, and blood samples were collected at time intervals of 0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 10, 12, and 24 h after dosing. The retention time of plasma, CLD, and VAL was found to be 2.7, 6.6, and 4.3 min, respectively. The result was validated statistically and by recovery studies. Linearity was acceptable in the range of 1-5 and 8-40 μg/mL for CLD and VAL, respectively. Maximal concentration (C max) of CLD and VAL was observed to be 338 ± 13.85 and 1282.21 ± 39.23 (ng/mL). The half-life of CLD and VAL was found to be 1.08 ± 0.21 and 1.43 ± 0.12 h, respectively. Conclusion The present method was successfully applied to the pharmacokinetic study of cilnidipine (CLD) and valsartan (VAL) in rat plasma after oral administration.